Analisis Komparatif Terhadap Aset Tak Berwujud Pada Perusahaan Multi Nasional dan Perusahaan Domestik: Penelitian - Hasiandra Simanjuntak; Jekky Ginting; Anita Br Saragih; William Girsang; Al Wahfi Suhada Sipahutar (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This study aims to comparatively analyze the tax treatment of intangible assets between multinational corporations (MNCs) and domestic companies, and its implications for the fairness and effectiveness of the Indonesian tax system. Using a qualitative approach with a descriptive-comparative design, this study examines the differences in principles, recognition mechanisms, amortization, and transfer pricing practices related to intangible assets based on national regulations and OECD international guidelines. The analysis shows that MNCs have greater flexibility in optimizing the global tax structure through profit shifting and asset allocation practices to low-tax jurisdictions, while domestic companies operate within a simpler and more limited regulatory framework. This disparity results in significant differences in effective tax rates (ETR) and potential erosion of the national tax base. This study emphasizes the importance of strengthening transfer pricing audit capacity, implementing the DEMPE framework, and international cooperation through Country-by-Country Reporting to create a fair and sustainable tax system.